Impact of depression and anxiety on health-related quality of life changes over time within individuals with rheumatoid arthritis or inflammatory bowel disease: A prospective Canadian cohort study - Carol A. Hitchon; Charles N. Bernstein; James M. Bolton; Casandra Dolovich; Renee El-Gabalawy; Lesley A. Graff; Lisa M. Lix; James J. Marriott; John D. Fisk; RuthAnn Marrie (PLoS ONE, 2026)
Objectives In individuals with rheumatoid arthritis (RA), inflammatory bowel disease (IBD), or primary depressive or anxiety disorders without RA or IBD (DEP/ANX) we aimed to evaluate between-person and within-person changes in physical and mental health-related quality of life (HRQoL) over time. We also aimed to compare the impacts of depression and anxiety symptoms on HRQoL, and to examine the roles of physical and cognitive functioning, fatigue, physical comorbidities, and disease activity, on HRQoL over time. Methods As part of a single centre prospective cohort study, individuals with RA (n = 154), IBD (n = 247), or DEP/ANX (n = 306) recruited between November 2014 and July 2016 were seen annually for 3 years. Participants reported symptoms of depression and anxiety (Hospital Anxiety and Depression Scale), fatigue (Daily Fatigue Impact Scale), HRQoL (RAND-36), and completed functional assessments (physical: nine-hole peg test, timed 25-foot walk test; cognition: Symbol Digit Modalities Test). Generalized linear models with generalized estimating equations tested between-person and within-person associations of depression and anxiety with HRQoL in covariate-adjusted models that included socio-demographic characteristics, health status and medication use. Physical (PCS-36) and mental (MCS-36) HRQoL were assessed separately and comparatively for RA, IBD and DEP/ANX. Results RA participants were older than IBD or DEP/ANX participants [mean age = 59.49(11.66), 47.45(14.80), 43.87(12.94)]. Most participants (>85%) reported meaningful changes in HRQoL. After adjustment, within-person increased depressive and anxiety symptoms were associated with reduced MCS-36 [depression: −7.91 (−9.45, −6.36), anxiety: −5.62 (−6.85, −4.39)]. Increased fatigue and worse cognition were associated with reduced PCS-36 [−0.33 (−0.38, −0.28); −0.31 (−0.64, 0.022)]. After adjustment, increased physical function, IBD or DEP/ANX diagnosis were associated with higher PCS-36 [1.47 (0.63, 2.30); 2.84 (1.60, 4.08); 5.23 (3.92, 6.55)]. Conclusions Variations in depression, anxiety, fatigue, cognition, and physical function are associated with HRQoL fluctuations in people with RA, IBD and DEP/ANX, highlighting the importance of addressing these issues while treating disease.